Recombinant bacteriophages containing the integrated transforming provirus of Gardner--Arnstein feline sarcoma virus. - Fedele, L A (1981)
The integrated DNA provirus of the Gardner-Arnstein (GA) strain of feline sarcoma virus (FeSV) was molecularly cloned in a bacteriophage lambda vector. The cloned DNA fragment is 14.4 kilobase pairs long and contains a 6.7-kilobase provirus flanked by cellular sequences derived from nonproductively transformed mink cells. Transfection of mouse NIH/3T3 cells with the cloned DNA fragment induced foci of transformation at efficiencies of 10(4) focus-forming units/pmol of sarcoma virus DNA. Restriction endonuclease mapping and heteroduplex analyses were used to compare the GA-FeSV provirus with that of Snyder-Theilen (ST)-FeSV, a second strain that contains homologous transformation-specific sequences (v-fes). Both viruses have the general structure 5'-gag-fes-env-c region-3', each having retained portions of the feline leukemia virus (FeLV) gag and env genes. In addition to segments shared by the two sarcoma viruses, GA-FeSV contains 1.7 kilobases of extra sequences not found in ST-FeSV. Of these, at least 400-500 base pairs located near the 5' end of v-fes encode a portion of the GA-FeSV polyprotein; the remaining 1.2 kilobases are derived from the FeLV env gene but do not appear to encode any detectable product related to the FeLV envelope glycoprotein. The close homology of the v-fes sequences shows that GA- and ST-FeSV were formed by recombination of FeLV with similar portions of a cat cellular gene (c-fes).